Efektivitas Trichoderma Harzianum dalam Meningkatkan Kualitas Kompos Berbasis Limbah Kulit Pisang - Putri, Rinni Rulma; Putri, Santi Diana; Amelia, Kiki; Sari, Wilna (UNIVERSITAS LABUHANBATU, 2024)
Compost is the result of organic fermentation that enriches soil nutrients naturally and is environmentally friendly. Banana peels have the potential to compost raw materials that are rich in nutrients, so far they are often wasted. Banana peel compost decomposed organic matter with the microorganism Trichoderma harzianum to improve the quality of banana peel-based compost. Its main purpose is to speed up the decomposition process and improve the nutritional quality of compost. This research was used to make compost from banana peels, with the addition of Trichoderma harzianum. The result is banana peel compost with nitrogen (N) content of 2.07% and potassium (K) of 5.02%, according to organic fertilizer quality standards in Indonesia. The population of microorganisms in compost varies, peaking at 16.4 x 107 cfu/gram and low at 11.6 x 108 cfu/gram. During composting, there is a significant change in pH. Initially, the pH is close to neutral (6.8), but drops dramatically to 4.9 by day 5. After this period, the pH increases again until it reaches 7.0 from day 16 to day 21. The results showed that composting banana peel waste with the addition of Trichoderma harzianum was effective in improving compost quality and producing products that conform to standards. Trichoderma harzianum can speed up the decomposition process, improve nutrient quality, and produce compost with an appropriate C/N ratio. Keywords: decomposition, compost, banana peel waste, Trichoderma harzianum